Initiation of insulin adjustment for carbohydrate at onset of diabetes in children using a home‐based education programme with a bolus calculator. (28th January 2016) - Thom, H; Greene, S; Alexander, V; Ramsay, V; Bluff, S; McKenzie, L; Sturrock, C; Conway, NT
Abstract: Improved glycaemic control following diagnosis of type 1 diabetes is associated with improved control in the longer term. This study reports on the experience of a paediatric diabetes service that introduced insulin adjustment for blood glucose and carbohydrate meal content from the first day of diagnosis. This is provided via a newly‐designed home education programme, using multiple daily injections of insulin, supported by a bolus calculator blood glucose meter. Glycaemic control was compared between patients who received the new programme (those diagnosed July 2012 to March 2014) to two historical cohorts: January 2000 to December 2009 and January 2010 to June 2012. The primary outcome was HbA1c at 4–6 months post‐diagnosis. Secondary outcomes were HbA1c at 10–12 months post‐diagnosis and the percentage of patients achieving HbA1c of <58mmol/mol in the first 12 months. Twenty‐seven children (16 male, mean age 9.7 ± 3.1) completed the new education package beyond 12 months. HbA1c was significantly lower in the 2012–14 cohort when compared to the 2000–09 and 2010–12 cohorts at 4–6 and 10–12 months (mean [95% CI] mmol/mol: 4–6 months 52[47–57] vs 68[65–71] vs 65[61–68]; 10–12 months 57[53–61] vs 72[70–75] vs 71[67–76] p < 0.001). In all, 89% of those diagnosed in 2012–14 achieved HbA1c <58mmol/mol within the 12 months post‐diagnosis compared with 39% in the 2010–12 cohort and 45% in the 2000–09 cohort (p < 0.001). In conclusion, carbohydrate counting with the use of a bolus calculator blood glucose meter at diagnosis was successfully introduced to a home‐based education programme. This approach has improved glycaemic control in the first year of diagnosis, which may have a positive impact on long‐term glycaemic control. Copyright © 2016 John Wiley & Sons.